Molecular packing and electronic processes in amorphous-like polymer bulk heterojunction solar cells with fullerene intercalation - Hu, Xiao (2014)
The interpenetrating morphology formed by the electron donor and acceptor materials is critical for the performance of polymer:fullerene bulk heterojunction (BHJ) photovoltaic (PV) cells. In this work we carried out a systematic investigation on a high PV efficiency (>6%) BHJ system consisting of a newly developed 5,6-difluorobenzo[c]1, 2, 5 thiadiazole-based copolymer, PFBT-T20TT, and a fullerene derivative. Grazing incidence X-ray scattering measurements reveal the lower-ordered nature of the BHJ system as well as an intermixing morphology with intercalation of fullerene molecules between the PFBT-T20TT lamella. Steady-state and transient photo-induced absorption spectroscopy reveal ultrafast charge transfer (CT) at the PFBT-T20TT/fullerene interface, indicating that the CT process is no longer limited by exciton diffusion. Furthermore, we extracted the hole mobility based on the space limited current (SCLC) model and found that more efficient hole transport is achieved in the PFBT-T20TT:fullerene BHJ as compared to pure PFBT-T20TT, showing a different trend as compared to the previously reported highly crystalline polymer:fullerene blend with a similar intercalation manner. Our study correlates the fullerene intercalated polymer lamella morphology with device performance and provides a coherent model to interpret the high photovoltaic performance of some of the recently developed weakly-ordered BHJ systems based on conjugated polymers with branched side-chain.